Flexural behavior of novel profiled steel-UHTCC assembled composite bridge decks - Chen, Yun-Long; Tong, Jing-Zhong; Li, Qing-Hua; Xu, Shi-Lang; Gao, Wei; Liu, Xin (Journal of constructional steel research, 2024)
Ultra-high toughness cementitious composite (UHTCC) has been noticed in the application of composite bridge deck (CBD) structures to avoid tensile cracks, benefiting from its excellent crack resistance behavior and characteristic of tensile strain hardening. In this study, a novel profiled steel-UHTCC assembled CBDs was proposed by adopting duplicate profiled steel parts that integrated the Perfobond rib (PBL) shear connector onto their top flange plates, which will improve fabrication convenience and economic efficiency. The flexural behavior of the assembled CBDs was investigated. Four specimens assembled respectively with T-shaped, Z-shaped, B-shaped, and H-shaped profiled steel parts were designed and fabricated. The failure modes, load-deflection curves, strain distributions, and slippage situations of four specimens were monitored and discussed. Then, the theoretical analyses on the shear connection degrees and ultimate flexural capacities of the assembled CBDs were performed, and a theoretical formula was proposed for calculating the ultimate flexural capacity. Finite element (FE) models of the assembled CBDs were established via ABAQUS software and validated against the test results. Ten groups of FE examples were designed for the detailed study of several key design parameters including shear span length, PBL hole diameter, thickness of UHTCC slab, thickness of steel web, and normalized PBL hole numbers. Finally, the proposed theoretical formula was validated using experimental and simulated results, demonstrating the validity of the proposed formula. •UHTCC can achieve high toughness and excellent cracking-resistant performance.•A novel composite bridge deck assembled by duplicate steel parts is proposed.•Flexural behavior of the novel assembled decks is explored via four flexural tests.•A parametric study is conducted to reveal the ultimate capacity.•A simplified formula for ultimate capacity is proposed with satisfactory accuracy.